Comportamiento agronómico y composición química de variedades de Bruchiarias y Megathyrsus maximus". - Pilco Herrera, Luis Javier (2017)
The present research was carried out in the Experimental Center "La Playita", of the Technical University of Cotopaxi, in the province of Cotopaxi. The investigation lasted 4 months. The treatments studied are described below: Brachiarias pasture: B. decumbens, B. mulato, B. brizantha. Pasture Savoy or Megathyrsus maximus s: Mombasa, Tanzania and Tobiata. State of maturity: 25, 50 and 75 days. In the simple effect, the highest height among the Megathyrsus maximus pastures evaluated was recorded with the mombasa with 121.63 cm and among the Brachiarias, B. decumbens showed the highest plant height with 83.33 cm. Forage production was Tanzania with 575.84 g m2 in Megathyrsus maximus and in Brachiarias B. decumbens forage production reported the highest value with 469.17 g m2. At 75 years of age the Brachiarias pastures with maturity stages were expressed as B, decumbens with 99.75 cm, and the highest forage weight was 764.50 g m2 for Megathyrsus maximus cultivars in the variable plant height, shows similarity in values at 50 and 75 days between tanzania and mombasa with 142.61 and 146.33 cm. The highest production was at 50 days with 877.64 g m2 for mombasa grass. The best biomass uptake response was obtained by h-1 with the Maralfalfa grass, followed by the King grass purple grass. In the bromatological analysis, the highest protein value was at 25 days in B. brizantha with 19.49%; while fiber maintained the low level with 34.90%, the cultivars of Megathyrsus maximus optimal protein levels were in Tanzania at 50 days with 16.92% and the lowest fiber was at 25 days with the same cultivar.